2017
DOI: 10.1021/acs.inorgchem.7b01311
|View full text |Cite
|
Sign up to set email alerts
|

Selective Incorporation of Primary Amines into a Trizirconium Imido System and Catalyic Cyclization of Aminoalkynes

Abstract: The trinuclear zirconium imido complex [{LZr(NMe)}] (2, L = CMeCHCHN) was synthesized by amine elimination between Zr(NMe) and endo-olefinic isomers of (tetramethylcyclopentadienyl)ethanamine (LH) (1). To study the fundamental reactivity of the trizirconium system, reactions of 2 with primary amines were examined. Selective incorporations of the primary amines were observed, depending on steric and electronic natures of the amine substrates. The amine-incorporated complexes [(LZrNHR)(LHZrNHR)(LHZr)(μ-NHR)(μ-NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The Brønsted acid-promoted reaction of β-(2-aminophenyl)-α,β-ynones with ketones was expanded to activated carbonyl compounds, such as β-ketoesters and β-diketones. The carbonyl group at position 3 of the quinoline nucleus could further react with the other keto functionality in the alkyl substituent at position 4, generating an additional [ 3 , 4 ]-fused six-membered ring whose structure depends on the type of β-dicarbonyl compound used. Indeed, for β-ketoesters, a thorough screening of reaction conditions revealed that catalytic amounts of p -TsOH·H 2 O were sufficient to efficiently promote a cascade double cyclization leading to 4 H -pyrano [3,4- c ]quinoline-4-one derivatives 77 .…”
Section: Sequential Reactions Of β-Aminoalkynes With Carbonylsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Brønsted acid-promoted reaction of β-(2-aminophenyl)-α,β-ynones with ketones was expanded to activated carbonyl compounds, such as β-ketoesters and β-diketones. The carbonyl group at position 3 of the quinoline nucleus could further react with the other keto functionality in the alkyl substituent at position 4, generating an additional [ 3 , 4 ]-fused six-membered ring whose structure depends on the type of β-dicarbonyl compound used. Indeed, for β-ketoesters, a thorough screening of reaction conditions revealed that catalytic amounts of p -TsOH·H 2 O were sufficient to efficiently promote a cascade double cyclization leading to 4 H -pyrano [3,4- c ]quinoline-4-one derivatives 77 .…”
Section: Sequential Reactions Of β-Aminoalkynes With Carbonylsmentioning
confidence: 99%
“…Their behavior changes by activation of the C-C triple bond by a metal catalyst. Various biologically important nitrogen heterocycles were directly synthesized in an easy way by means of intramolecular hydroamination of aminoalkynes in the presence of several transition metal as well as lanthanide catalysts [ 4 , 5 ]. The aptitude to form π- and σ-complexes can help in the choice of catalysts for the desired transformations when bi- or polyfunctional substrates are involved [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonyl group at position 3 of the quinoline nucleus could further react with the other keto functionality in the alkyl substituent at position 4, generating an additional [3,4]fused six-membered ring whose structure depends on the type of β-dicarbonyl compound used. Indeed, for β-ketoesters, a thorough screening of reaction conditions revealed that catalytic amounts of p-TsOH•H 2 O were sufficient to efficiently promote a cascade double cyclization leading to 4H-pyrano [3,4-c]quinoline-4-one derivatives 77.…”
Section: Conversely Isomerization Of the Iminium Ion Intermediate [I]...mentioning
confidence: 99%
“…Their behavior changes by activation of the C-C triple bond by a metal catalyst. Various biologically important nitrogen heterocycles were directly synthesized in an easy way by means of intramolecular hydroamination of aminoalkynes in the presence of several transition metal as well as lanthanide catalysts [4,5]. The aptitude to form πand σ-complexes can help in the choice of catalysts for the desired transformations when bi-or polyfunctional substrates are involved [6].…”
Section: Introductionmentioning
confidence: 99%